2011
DOI: 10.1007/s11262-011-0633-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of highly pathogenic H5N1 avian influenza viruses isolated from poultry farms in Egypt

Abstract: Twenty-four avian influenza viruses were collected from poultry farms in three different governorates in Egypt during the years 2006-2009 and genetically characterized. All the isolates were confirmed to be type A and subtype H5 influenza virus by chromatographic strip test and hemagglutination inhibition assay. The sequence and phylogenetic data revealed that all Egyptian isolates cluster together and belong to subclade 2.2.1 of the H5N1 virus of Eurasian origin. Within the clade, Egyptian isolates were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Here, for the first time, the isolation of H9N2 virus in Egypt is described. Despite previous intense surveillance activities conducted by our team and others in the context of H5N1 endemicity in Egypt, H9 viruses had not been detected before [6,7,13,22]. In the present investigation, close sequence and phylogenetic identities with the G1-like H9N2 virus currently circulating in the neighbouring countries could indicate further spread of the virus into Egypt as a part of its extensive circulation in the nearby countries rather than a separate introduction from the Eastern Asian AIV epicentre.…”
contrasting
confidence: 54%
“…Here, for the first time, the isolation of H9N2 virus in Egypt is described. Despite previous intense surveillance activities conducted by our team and others in the context of H5N1 endemicity in Egypt, H9 viruses had not been detected before [6,7,13,22]. In the present investigation, close sequence and phylogenetic identities with the G1-like H9N2 virus currently circulating in the neighbouring countries could indicate further spread of the virus into Egypt as a part of its extensive circulation in the nearby countries rather than a separate introduction from the Eastern Asian AIV epicentre.…”
contrasting
confidence: 54%
“…On the contrary, poultry industry still is in strong need of more aggressive bio-security measures, monitoring of the susceptible and already vaccinated poultry flocks. These speculations go along with El-Zoghby et al [25] and Eladl et al [29].…”
Section: Oligonucleotide Primerssupporting
confidence: 60%
“…On the contrary, viruses cluster in clade 2.2.1.1, also known as variant 2.2.1 viruses, had extensive amino acids substitutions in or adjacent to the immunogenic epitopes at the proximal globular head region of the HA protein which could enable continuous circulation of the virus in and among commercial poultry despite large scale vaccination campaigns [16,17]. Regular nationwide active, passive and targeted surveillance revealed that HPAV H5N1 is perpetuated in many commercial farms, backyards and live bird markets (LBM) [4,7,9,16,18]. Culling of infected birds occurs infrequently in Egypt [6].…”
Section: Resultsmentioning
confidence: 99%